The Study of Change in Consumer Behavior towards Agricultural Marketing (International Journal of Food and Nutritional Sciences, 2022)
Present study was confined to one of the districts of Maharashtra known for its agricultural progressiveness, dynamic agricultural marketing and consumer with reasonable awareness and proportionate sensitivity for agricultural marketing in particular. In the present study 150 respondents from low, medium and high income category of consumers for agricultural marketing were interviewed. The association of consumer behavior with selected features was found.